DECENTRALIZATION THROUGH INNOVATION: THE AUTHORIAL MODEL OF HOUSEHOLD SOLAR CLUSTERING AND ENERGY RESILIENCE IN WAR-AFFECTED UKRAINE - Rychka, Roman (European Journal of Interdisciplinary Issues, 2025)
The full-scale military aggression against Ukraine has exposed the structural fragility of centralized energy systems, transforming energy infrastructure into a primary target of hybrid warfare. This context has intensified the need for energy resilience solutions that extend beyond conventional renewable deployment toward fundamentally decentralized architectures. This article examines an original authorial model of energy decentralization developed and implemented by the author, which is based on the systematic clustering of household-scale solar photovoltaic (PV) installations within individual territorial communities. Unlike spontaneous prosumer-driven diffusion, the model analyzed in this study represents a deliberately designed and strategically implemented approach that utilizes private residential buildings as spatial platforms for distributed generation. The model was conceptualized and operationalized in the Dnipropetrovsk region of Ukraine beginning in 2018 – before the full-scale invasion – and was subsequently subjected to an unprecedented wartime stress test. Through the coordinated deployment of hundreds of household solar power plants, aggregated at the community level but dispersed spatially, the model achieves generation capacities comparable to small industrial facilities while substantially reducing vulnerability to targeted military strikes and large-scale grid failures. Methodologically, the study employs a single-case research design combining policy analysis, regional statistical data, media documentation, and aggregated operational evidence from the implementation process. The findings demonstrate that the early and systematic application of this authorial model contributed to the emergence of the Dnipropetrovsk region as a national leader in household solar generation, with sustained growth before and during the war. The results further indicate that the clustered household approach provides measurable advantages in terms of infrastructural survivability, local voltage support, and socio-economic stabilization of rural communities. The article argues that the model developed by the author constitutes an original and significant contribution to the field of decentralized energy systems. Beyond its relevance for Ukraine’s wartime resilience and post-war recovery, the model offers a transferable framework for regions facing geopolitical instability, climate-related disruptions, or systemic risks inherent in centralized power infrastructures.